Oyster Crassostrea gigas, a good model for correlating viral and chemical contamination in the marine environment. (November 2021) - Fiorito, Filomena; Di Concilio, Denise; Lambiase, Sara; Amoroso, Maria Grazia; Langellotti, Antonio L.; Martello, Anna; Esposito, Mauro; Galiero, Giorgio; Fusco, Giovanna
Abstract: To establish a relationship between viruses and chemicals, they were analysed in oyster Crassostrea gigas from an Italian experimental station. The chemicals concentrations were: Σ6 NDL-PCBs 0.82–7.12 ng g −1 ; BaP LOQ (<0.2 μg kg −1 ) to 1.2 μg kg −1 ; PAH4 LOQ (<0.2 μg kg −1 ) to 9.8 μg kg −1 ; Cd 0.073–0.365 mg kg −1 ; Pb 0.010–0.487 mg kg −1 ; and Hg < LOQ (0.089 mg kg −1 ). The viruses identified included: noroviruses (NoVGI/GII), astrovirus (AsV), rotavirus (RV), adenovirus (AdV), and sapovirus (SaV), while hepatitis A, hepatitis E, and Aichi viruses were not detected. Significant correlations were observed for NDL-PCBs with NoVGI, NoVGII, and AdV; BaP and PAH4 with NoVGI and AsV; Cd with RV; Pb with NoVGI and AsV; PAHs with Pb; AsV with NoVGI; and AdV with NoVGII. The study indicated as C. gigas is a model for correlating pollutants and foodborne viruses, whose co-presence may represent an additional food safety risk. Graphical abstract: Unlabelled Image Highlights: Oysters accumulated NDL-PCBs, PAHs as well as Cd and Pb. Oysters accumulated NoV (GI/GII), RV, AsV, SaV and AdV. HAV, HEV and AiV were not detected in oysters. Levels of viral and chemical contaminants in oysters showed seasonality. Correlation between viral and chemical contaminants in oysters was found.